Association between vitamin D receptor gene variants and neonatal sepsis: A systematic review and meta‐analysis - Darnifayanti Darnifayanti; Diva Rayyan Rizki; Shakira Amirah; Muhammad Fahd Abdurrahman; Muslim Akmal; S.N. Abdulmadjid; Sulaiman Yusuf; Muhammad Iqhrammullah (Elsevier, 2024)
The objective of this systematic review and meta-analysis was elucidating the association of VDR SNPs (FokI, TaqI, BsmI, BgII, and ApaI) with neonatal sepsis. Literature search was performed to retrieve records published until August 2nd, 2023 (PROSPERO registration: CRD42023451355). Meta-analysis was carried out to determine the pooled estimates for Odds Ratio (OR). A total of four studies were included with 500 neonates (250 sepsis cases and 250 healthy controls). There was an association observed between TaqI SNP with neonatal sepsis for CT vs. CC+TT (OR=1.95) and TT vs CT+CC (OR=0.40). Moreover, the pooled estimates also suggested that CC vs. CT+TT (OR= 0.37) and C vs. T (OR=0.66) of FokI SNP were significantly associated with neonatal sepsis. SNP of BgII was found to be significantly associated with neonatal sepsis, but only reported in a single study.